EDUKASI STUNTING PADA ANAK SEKOLAH DALAM PEMILIHAN SUMBER GIZI MAKANAN DI KELURAHAN SABUNGAN JAE TAHUN 2023 - Arinil Hidayah; Khairunnisa Butar - Butar; Elmi Sahriani; Anita Amelia (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
Stunting is one of the most significant obstacles in producing quality human resources in every country. Stunting is a growth and development disorder experienced by children under five due to long-term malnutrition, recurrent infectious diseases, and lack of psychosocial stimulation. Stunting events can be prevented starting from adolescence, where teenagers are the generation of prospective mothers and prospective fathers, so it is necessary given good knowledge about balanced nutrition and choosing the right food to prevent stunting from an early age. One effort to increase teenagers' knowledge is by providing nutrition education. Nutrition education is very necessary to increase adolescent nutritional knowledge, form a positive attitude towards nutritious food in order to form good eating habits. The more they have good nutritional knowledge, the more an individual will consider the type and quality of food they choose to consume. In the first stage the material provided is balanced nutrition for teenagers and in the second stage the material is selecting the right menu in accordance with the principles of balanced nutrition. there is an increase in skills in preparing healthy daily menu choices and paying attention to the principles of balanced nutrition. All participants were enthusiastic in taking part in the activity.